A theoretical 4-stage shear model for single-lap torqued bolted-joint with clearances. (15th February 2018) - Kou, Jianfeng; Xu, Fei; Xie, Wei; Zhang, Xiaoyu; Feng, Wei
Abstract: In this paper, a theoretical 4-stage shear model for a single-lap torqued bolted-joint with clearance is proposed. The deformation mechanism of the bolted-joint indicates that the contact status is the key factor for the nonlinearity of the load-displacement curve. On the basis of the contact status, the expression of this model and its parameters are proposed. Compared with the previous Tri-linear model, this model is improved on three aspects. First, the 1st stage of the model has been improved by using the partial slip theory. Second, an additional 2nd stage is considered for taking into account the asynchronous slip of the interfaces between components and between bolt head and component. Third, the 4th stage of this model is derived from the elastic foundation beam model and the Cai-Shan Liu's approximate contact model. Moreover, the 4-stage shear model is validated by 3-D detailed FE-models. The results show that the 4-stage model can correctly describe the shear behavior, especially the nonlinearity of the load-displacement curve in the 1st stage and the 4th stage. In addition, the effects of clearance and bolt length on the joint stiffness in each stage are presented.